2016
DOI: 10.15244/pjoes/61701
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Environmental Efficiency and Agricultural Environmental Kuznets Curve Based on Technological Gap: the Case of China

Abstract: With regards to the interchanging features of agricultural pollution and its negative impacts on China's eco-environment such as environmental degradation, this paper, by fully taking into consideration the gap in environmental technology, incorporated the extended SBM directional distance function and Metaconstraints effi ciency function to estimate China's agricultural environmental effi ciency (roughly three regions: eastern, central, and western China), and employed the panel model to study the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Poverty and reduction of ecological assets are highly coupled in rural China (Cao et al, 2015). Some case studies showed that the economic development and environment follow the inverted U shape of the environmental Kuznets Curve (Hassan et al, 2015; Zambrano‐Monserrate and Fernandez, 2017; Wang and Shen, 2016; Mao et al, 2013; Li et al, 2016; Zhang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Poverty and reduction of ecological assets are highly coupled in rural China (Cao et al, 2015). Some case studies showed that the economic development and environment follow the inverted U shape of the environmental Kuznets Curve (Hassan et al, 2015; Zambrano‐Monserrate and Fernandez, 2017; Wang and Shen, 2016; Mao et al, 2013; Li et al, 2016; Zhang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…To further grasp the research trends in this research field, we needed to conduct data mining of the literature in more depth to capture key information and analyze its research hotspots. According to data from Web of Science, by the end of 2021, the top three countries in terms of the number of papers on AEE research were China (47), France (12), and the United States (22), followed by Germany, Greece, Italy, Australia, Sweden, Ireland, and the Netherlands (Table 2). Research on AEE has attracted extensive attention in various fields.…”
Section: An Overview Of Aee Researchmentioning
confidence: 99%
“…According to data from Web of Science, by the end of 2021, the top three countries in terms of the number of papers on AEE research were China (47), France (12), and the United States (22), followed by Germany, Greece, Italy, Australia, Sweden, Ireland, and the Netherlands (Table 2). Research on AEE has attracted extensive attention in various fields.…”
Section: An Overview Of Aee Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The first national survey of pollution sources in the year of 2010 in China shows that total agricultural chemical oxygen demand, total nitrogen, and total phosphorus emissions from agricultural production activities accounted for 43.7 percent, 57.2 percent, and 67.4 percent of total emissions, respectively, indicating that agricultural pollution has exceeded industrial pollution and become the largest source of pollution in China. Agricultural pollution will cause a series of environmental problems, such as water eutrophication (Edgardo and Robert 2018), groundwater pollution (Ma et al 2018), loss of biodiversity (Muditha and Clevo 2017), soil acidification and consolidation (Guo et al 2010; Sebnem 2017), which can threaten food safety, human health, and sustainable agricultural development (Wang and Shen, 2016).…”
mentioning
confidence: 99%